Analysis of Settlement Availability at Manyar Economic District Strategic Area of Gresik Regency - Anak Agung Sagung Alit Widyastuty; Annisa Budhiyani Tribhuwaneswari; Lutfi Zulkarnain (Jurnal Kawistara, 2021)
Rapid development and increasing population density have created challenge for many regions to provide settlement spaces. The demand for settlement requires analysis that can forecast on the availability of space and the growth of settlement. Such a challenge is faced by Manyar sub-district of Gresik regency. Since it became an Economic Strategic District Area in the agroindustry area in Gresik Regency, the demand for settlement at Manyar increased following the 2017 population boom. Manyar is recorded as the third maximum growth in Gresik regency with numbers of 114.056 inhabitant living in 9.542 acre. This study aims to examine the facilities and infrastructure, as well as the availability of residential land in the next 20 years. This study uses quantitative technique that includes projections of settlement demand. Data collection methods takes the form of field observations and surveys of related agencies. The analytical technique utilized was backlog and scalogram study regarding the availability of settlement, facilities and infrastructure support. As the result, this paper found that the population growth rate of Manyar sub-district reaches 0.1% every year. Consequently, the settlement and supporting infrastructures required at the year 2039 increase massively since 2019 consists of housing facilities, education, health facilities, worship facilities, commerce and services facilities, and green open spaces. The land required for the development of the facility is 269.1 acre. Based on the level of need for residential facilities and infrastructure in the next 20 years in Manyar sub-district, further research is needed to anticipate the phenomenon of pond land conversion by maintaining land functions.